Motivation for educational and research activities as a factor in the development of andragogical subjectivity of undergraduates - Kolumbayeva, Sholpan; Советканова, Дамира; Kosshygulova, Aliya (Pedagogy and Psychology, 2023)
The radical changes in social, political and economic life that have taken place in our country over the past decade require specific transformations in many social spheres, especially in the system of higher professional education. Today, new concepts of higher education are being developed, in which humanistic ideals, universal values, principles of democratization, humanization and humanitarization of higher education are proclaimed as the leading ones. The time of changing technologies has accelerated in relation to the life of generations, the information flow doubles every 5-10 years, this phenomenon in scientific thought was designated as a change in the reference frequencies of biological and social time. In modern society, in order to keep up with technological and intellectual progress, it is necessary to constantly learn and improve skills. As part of the revitalization of the European system of higher education and the introduction of three-level education, higher education is faced with the task of training personnel in active creative activity and quick adaptation to new, often changing conditions. Consequently, it is obvious that in psychology and pedagogy there have been outlined strategies for the development of the subject capabilities of students, which is reflected in the development of a model of their vocational education system. First of all, this is relevant for the sphere of higher education, where the development of the subjective qualities of a person becomes a priority, allowing him to live in a changing world and transform himself in it.